Development of M-Learning Media Illustrated Crossword Puzzles to Increase Learning Motivation for Middle School Students - Wardi Syafmen; Silfiani Indri (Universitas Negeri Makassar, 2023)
this study aims to produce M-Learning learning media illustrated with crossword puzzles assisted by Google Sites to increase student motivation in class VII SMP and describe the feasibility of the media in terms of validity, practicality, and effectiveness. This research is a development research using the ADDIE model, which includes analyze, design, development, implementation, and evaluation stages. The results showed that the quality of M-Learning learning media illustrated with crossword puzzles assisted by Google sites to increase student motivation, for the validation aspect of M-Learning was categorized as valid with a validity of 75%. For the practicality questionnaire, the teacher response questionnaire obtained 91.67% of the very practical criteria and the 9 student response questionnaire was 90.40% with very practical criteria, so M-Learning was stated to be very practical. For the aspect of effectiveness, it can be seen from the results of the study tests where all students passed or met the KKM, student response questionnaires with a percentage of 90.20% were very effective criteria. And the N-Gain value of 0.76 indicates that there is an increase in learning motivation in the high category, so that M-Learning is effective for increasing student motivation.